Contributions to the 4th young scientists workshop on agricultural development in Central and Eastern Europe - Raushan Bokusheva; Gertrud Buchenrieder (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2006)
This Discussion Paper contains the greater part of the contributions to the Young Scientists Workshop on Agricultural Development in Central and Eastern Europe (IAMO, September 4-5, 2006). After last years' positive response, the workshop has been organized for the fourth time and has a solid number of contributions. The aim of this annual event is to give young scientists the opportunity to present and discuss their transition-related research. The following short versions of the workshop contributions serve as a basis for discussion during the workshop, but also offer a cross-sectional overview of current research being carried out by young scientists. Although the issues covered by the workshop contributions are quite diverse, they share a common interest in evaluating the impact of institutional and policy changes on agricultural and rural development at the current stage of transition. Regionally, the contributions focus on the new member states of the European Union, as well as countries of South Eastern Europe. – – Dieses Diskussionspapier enthält den größten Teil der Beiträge, die im Rahmen des Workshops zur Agrarentwicklung in Mittel- und Osteuropa für Doktoranden und kürzlich auch Promovierte vorgestellt und diskutiert werden. Dieser Workshop findet zum vierten Mal am IAMO statt, dieses Jahr vom 4. bis 5. September. Ziel der Veranstaltung ist es, Nachwuchswissenschaftlern die Möglichkeit zu geben, ihre Forschungsvorhaben zu präsentieren und zu diskutieren. Die folgenden Kurzfassungen sollen allerdings nicht nur als Diskussionsgrundlage für den Workshop dienen, sondern auch einen kleinen Überblick über die gegenwärtige Nachwuchsforschung im Agrarbereich zu Mittel- und Osteuropa vermitteln. Auch wenn die Workshopbeiträge ein sehr breites Themenspektrum abdecken, beschäftigen sie sich alle mit der Analyse der Wirkung von politischen und institutionellen Änderungen auf die Entwicklung ländlicher Räume und des Agrarsektors im gegenwärtigen Stadium des Transformationsprozesses. Regional konzentrieren sich die Beiträge auf die neuen Mitgliedsländer der Europäischen Union und die Länder Südosteuropas.
urn:nbn:de:gbv:3:2-601
Keywords: 330